Genetic Influence on Frequencies of Myeloid-Derived Cell Subpopulations in Mouse - Krayem, Imtissal; Sohrabi, Yahya; Javorková, Eliška; Volkova, Valeriya; Strnad, Hynek; Havelková, Helena; Vojtíšková, Jarmila; Aidarova, Aigerim; Holáň, Vladimír; Demant, Peter; Lipoldová, Marie (Frontiers in Immunology, 2022)
Differences in frequencies of blood cell subpopulations were reported to influence the course of infections, atopic and autoimmune diseases and cancer. We have discovered a unique mouse strain B10.O20 containing extremely high frequency of myeloid-derived cells (MDCs) in spleens. B10.O20 carries 3.6% of genes of the strain O20 on the C57BL/10 genetic background. It contains much higher frequency of CD11b+Gr1+ cells in spleens than both its parents. B10.O20 carries O20-derived segments on chromosomes 1, 15, 17 and 18. Their linkage with frequencies of blood cell subpopulations in spleens was tested in F2 hybrids between B10.O20 and C57BL/10. We found 3 novel loci controlling MDC frequencies: Mydc1, 2 and 3 on chromosomes 1, 15 and 17, respectively, and a locus controlling relative spleen weight (Rsw1) that co-localizes with Mydc3 and also influences proportion of white and red pulp in spleen. Mydc1 controls numbers of CD11b+Gr1+ cells. Interaction of Mydc2 and Mydc3 regulates frequency of CD11b+Gr1+ cells and neutrophils (Gr1+Siglec-F- cells from CD11b+ cells). Interestingly, Mydc3/Rsw1 is orthologous with human segment 6q21 that was shown previously to determine counts of white blood cells. Bioinformatics analysis of genomic sequence of the chromosomal segments bearing these loci revealed polymorphisms between O20 and C57BL/10 that change RNA stability and genes’ functions and we examined expression of relevant genes. This identified potential candidate genes Smap1, Vps52, Tnxb and Rab44. Definition of genetic control of MDCs can help to personalize therapy of diseases influenced by these cells.